Error analysis of optoelectronic frequency response measurement of photodiodes using high-extinction ratio Mach-Zehnder modulator - Inagaki,K. (2015)
We analyze the errors of a newly proposed measurement method on optoelectronic frequency response of photodiodes, which uses a high-extinction ratio Mach-Zehnder modulator to generate a two-tone stimulus lightwave. Five major error factors are identified and analyzed quantitatively. The result shows that the evaluated combined uncertainty is expected to be less than 0.5 dB. © 2012 IEEE.